Young Lives: Andhra Pradesh Round 2 Survey: Summary - Galab, S; Reddy, P; Himaz, R (Young Lives, 2008)
This report presents initial findings from the second round of quantitative data collection which was carried out in Andhra Pradesh in late 2006 to early 2007. It aims to give a broad outline of some of the key indicators of childhood poverty and changes that have taken place in the children’s lives between the first round data collection in 2002 and this second round. Data are mainly presented for the entire age group cohort, in most cases separated into wealth groups or by rural/urban location. The data reflect the growth and poverty reduction witnessed in recent years. Also there is evidence that the Young Lives households have become better off over the four years of the survey. However, inequalities in wealth and consumption expenditure between castes and ethnic groups, and the incidence of poverty between urban and rural areas, and between different regions of AP, are reflected in the Young Lives sample. These disparities fell slightly between the two rounds but remained prominent in 2006. Parental education, caste and household size were important determinants of poverty. Households afflicted by drought before Round 1 data collection were also more likely to be worse off by the time of the Round 2 data collection. The full richness of the data is not contained in this report, but it gives enough information to prompt other researchers, policymakers and other stakeholders to start to engage with the data.